Application of mixed reality technology in talocalcaneal coalition resection - Zhang, Jieyuan; Wang, Cheng; Li, Xueqian; Fu, Shaoling; Gu, Wenqi; Shi, Zhongmin (Frontiers in Surgery, 2023)
Objectives: With positive outcomes recorded, the mixed reality (MR) technology has lately become popular in orthopedic surgery. However, there are few studies that specifically address the utility of MR in talocalcaneal coalitions (TCC) resection. Our goal in this retrospective study is to assess certain data while examining the viability of using MR to treat TCC resection. Methods: Six consecutive patients with TCC diagnosed by computed tomography (CT) for which nonoperative therapy had failed and MR system assisted TCC resection were included in this study from March 2021 to December 2021. The feasibility and accuracy of TCC resection were assessed by post-operation radiography. The American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot score and visual analog scale (VAS) score were used to assess the recovery condition and pain level pre- and post-operation. Results: The surgeon can accurately resect the TCC according to the preoperatively determined range by superimposing the holographic model with the actual anatomy of the TCC using an MR system. Additionally, no additional x-ray was necessary while operating. Mean follow-up was 10.3 months, with a minimum of 6 months. There is a significant difference between the preoperative AOFAS score of 53.4±3.8 and the 6-month follow-up AOFAS score of 97.3±2.2 (p＜0.05). There is also a significant difference between the preoperative VAS score of 8.1±0.7 and the 6-month follow-up VAS score of 1.7±0.4 (p＜0.05). All individuals had clinical subtalar mobility without stiffness following surgery. Conclusion: While the TCC resection operation is being performed, the application of MR technology is practicable, effective, and radiation-free, giving surgeons satisfactory support.